2012
DOI: 10.1007/s10661-012-2837-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal contamination in water, sediment and biota from a semi-enclosed coastal area

Abstract: This study identifies and quantifies the spatial variations of metal contamination in water, sediment and biota: the common cockle (Cerastoderma edule) and the Mermaid's glove sponge (Haliclona oculata), within a heavily anthropogenically impacted semi-enclosed estuarine-coastal area with a low ability to disperse and flush contaminants (Poole Harbour, UK). The results showed that metal contamination was detected in all environmental compartments. Water was polluted with As, and Hg sediment metals were mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 49 publications
1
16
1
1
Order By: Relevance
“…This is in agreement with previous literature on metal pollution in Poole Harbour by Langston et al [30], Aly et al [31], and Oaten et al [32], which reported generally higher metal concentrations within Holes Bay in sediment and seawater, as well as biota. F. spiralis metal concentrations at Sandbanks were also relatively high.…”
Section: Metal Contamination and Seasonal Variationsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previous literature on metal pollution in Poole Harbour by Langston et al [30], Aly et al [31], and Oaten et al [32], which reported generally higher metal concentrations within Holes Bay in sediment and seawater, as well as biota. F. spiralis metal concentrations at Sandbanks were also relatively high.…”
Section: Metal Contamination and Seasonal Variationsupporting
confidence: 93%
“…A study by Owen, et al [9] reported F. vesiculosus to begin exhibiting the gene for MT when exposed to a concentration of Cu of 30 µg/l. However, Cu concentrations in seawater in Poole Harbour do not exceed 3 µg/l [31]. For comparison, Zn, Fe, and Pb concentrations in F. vesiculosus from the Fal Estuary, Cornwall, were as much as an order of magnitude higher, with Cu two orders of magnitudes higher, compared to this study [56].…”
Section: Influences Of Mt Response and Variabilitycontrasting
confidence: 65%
See 1 more Smart Citation
“…This relatively shallow bay (mean depth 13.6 m, area 1930 km 2 ) is joined to Bass Strait through a 3 km-wide channel and contains areas with highly contaminated sediments due to historical and current industrial discharges through storm water run-off (Harris et al, 1996). Semi-enclosed coastal areas are contamination hotspots; with sediments remaining polluted, sometimes for decades after the primary source is removed due to restricted currents and wave action (Aly et al, 2012). Notably, little is known about the contaminant load in Little Penguins breeding at St Kilda and how it compares to that of conspecifics at less urban environments, such as the nearby Phillip Island colony and more remote Bass Strait island colonies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to physicochemical parameters and ecotoxicological assays, water monitoring should include the determination and quantification of metals (4)(5)(6). Although their impact has no visible influence compared to other pollutants, heavy metals can cause long-term effects on ecosystems (7) due to their persistence, bioaccumulation, and biomagnification in the food chain (8).…”
mentioning
confidence: 99%